PROEJA: uma análise das práticas direcionadas à turma de segurança do trabalho no IEEP a partir do documento base - AQUINO, Perla Sofia Andrade de (2023)
This essay presents an analysis related to the practices directed in the Work Safety/2016 class of IEEP, and the base document of PROEJA. It was developed through field research, qualitative nature, due to the subjectivity on relations and practices, through the internship afforded by PIBID (Programa Institucional de Bolsa de Iniciação à Docência). Moreover, methodological procedures used were participant observation, the non-directive interview with the pedagogical and course coordinators, and bibliographic research based on Freire (1983), Arroyo (1986), Haddad (2000), Ciavatta ( 2005) and Libaneo (2001) studies. In this sense, the main objective of this work is to explicit the duality between the practices developed in the reality of the course and the principles proposed by the base document. The specific objectives are: to analyze the relationship between the proposals presented in the Base Document and the practices in the course; expose the consequent factors of the dualism evidenced, through information given by the interview; and finally, to present a viable solution proposal to overcome the problematic. The study showed the importance of integration between the pedagogical coordination, course coordination and faculty for the planning and development of actions that contribute to the effectiveness of the principles and objectives of PROEJA, aiming to provide access and permanence, integrated training of students and teachers continuing training.